1998
DOI: 10.1046/j.1365-8711.1998.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical unifying scheme for gamma-ray bright blazars

Abstract: The phenomenology of gamma-ray bright blazars can be accounted for by a sequence in the source power and intensity of the diffuse radiation field surrounding the relativistic jet. Correspondingly, the equilibrium particle distribution peaks at different energies. This leads to a trend in the observed properties: an increase of the observed power corresponds to: 1) a decrease in the frequencies of the synchrotron and inverse Compton peaks; 2) an increase in the ratio of the powers of the high and low energy spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

105
1,016
6
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 923 publications
(1,132 citation statements)
references
References 36 publications
105
1,016
6
5
Order By: Relevance
“…In other words, theblazar sequence predicts the non-existence of high-frequency peaked, highly luminous BL Lac objects. A theoretical justification of these correlations is discussed in Ghisellini et al (1998). The concept of a Blazar sequence is an interesting but still debated idea (e.g., Ghisellini et al 2012;Padovani et al 2012).…”
Section: Blazar Sequencementioning
confidence: 99%
“…In other words, theblazar sequence predicts the non-existence of high-frequency peaked, highly luminous BL Lac objects. A theoretical justification of these correlations is discussed in Ghisellini et al (1998). The concept of a Blazar sequence is an interesting but still debated idea (e.g., Ghisellini et al 2012;Padovani et al 2012).…”
Section: Blazar Sequencementioning
confidence: 99%
“…Fossati et al (1998) presented the blazar sequence: the peak luminosity of the synchrotron component (L peak ) and the Compton dominance (the ratio of the peak of the Compton to the synchrotron peak luminosity) are anti-correlation with the synchrotron peak frequency ν peak . Ghisellini et al (1998) modeled the broadband spectra of blazars, and suggested that along the blazar sequence (BL Lacs → FSRQs), a stronger radiative cooling causes a particle energy distribution with a break at lower energies. So the synchrotron ⋆ E-mail: ynzx@yeah.net and Compton peaks shift to lower frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The latter population of photons can be the same synchrotron radiation (Synchrotron Self-Compton, SSC) or a source external to the jet, like the accretion disk or the broad-line region (External Compton, EC). and Ghisellini et al (1998) suggested that blazars follow a trend -the blazar sequence -where sources with low bolometric luminosity have both peaks at high frequencies (soft X-rays for synchrotron and TeV for IC), while, as the luminosity increases, both peaks shift to lower frequencies (optical/infrared for synchrotron and MeV/GeV for IC). See, however, Padovani (2007) and references therein for a discussion.…”
Section: Introductionmentioning
confidence: 99%